Redefining Lactose as a Conditional Prebiotic - Andrew Szilagyi (Canadian Journal of Gastroenterology)
Lactose in dairy products is maldigested by up to 70% to 75% of the world's population and many people may therefore suffer symptoms reminiscent of irritable bowel syndrome. As a result, most research to date has concentrated on ways of improving lactose tolerance to enhance dairy as a source of nutrition. However, research on other possible benefits of lactose and its maldigestion has lagged. In view of an exponential growth in the understanding of intestinal microfloral host interactions and the expanding therapeutical potential of probiotics, a reassessment of the role of lactose as a potential prebiotic in lactase nonpersistent subjects is required. Gibson and Roberfroid introduced the concept of prebiotics and outlined definitive requirements for such a compound. The present article examines scientific and clinical knowledge about the properties of lactose and argues that in lactase nonpersistent subjects, lactose qualifies as a prebiotic.